Intrabronchial Catheter Resuscitation for Respiratory and Cardiorespiratory Arrest. Issue 1 (July 2018) - Wolf, Jeffrey S.; Hebert, Andrea; Sanchez, Pablo; Wijesinha, Marniker; Shapiro, Scott; Morales, Robert; Iacono, Aldo T.
ABSTRACT: Introduction: We sought to determine whether intrabronchial oxygenation would provide adequate gas exchange during both anesthesia induced apneic and cardiopulmonary arrest and cardiac massage (CPR). Methods: Ten pigs underwent general anesthesia with mechanical ventilation. Blood gases were measured in each animal at 4 min intervals for up to 28 min. An intrabronchial catheter (4 L/min O2 ) was inserted through an endotracheal tube after respirator cessation. Group A animals (6) were resuscitated with the catheter but without CPR. Group B animals (4) were rendered apneic and cardioplegic and resuscitated by CPR for 28 min using the intrabronchial device. Results: All group A animals were resuscitated and survived after 24 min of apnea. Mean pO2 decreased from 378 mmHg (95% confidence interval [CI], 288–468) to 292 mmHg (95% CI, 246–339), P  = 0.009; pCO2 increased from 52 mmHg (95% CI, 43–61) to 137 mmHg (95% CI, 116–158), P  < 0.0001; and pH decreased from 7.32 (7.29–7.36) to 6.98 (6.92–7.03), P  < 0.0001. In a control animal bronchial catheter oxygen flow ceased at baseline and pO2 decreased from 268 to 30 mmHg by 20 min. In group B animals mean pO2 decreased from 426 mmHg (95% CI, 273–579) to 130 mmHg (95% CI, 92–168) after 28 min, P  < 0.0001; pCO2 increased from 49 mmHg (95% CI, 41–58) to 73 mmHg (95% CI, 61–86), P  = 0.03; and pH decreased from 7.34 (7.33–7.35) to 7.07 (6.98–7.16), P  < 0.0001. In the control receiving intratracheal oxygen pO2 decreased from 324 to 88 mmHg after 16 minu of CPR. Conclusions: Intrabronchial oxygenation provides sustained hyperoxemia during complete apnea and cardiac arrest with CPR.